Techniques of Survey of Vegetation Cover and Determination of Carrying Capacity - Ouled Belgacem, Azaiez; Neffati, Mohamed (International Center for Agricultural Research in the Dry Areas, 2024)
A training course on rangeland restoration and sustainable management was held at the Institut des Régions Arides Branch in Kebili on February 28-29, 2024, under the OneCGIAR Livestock and Climate Initiative. The course aimed to enhance the capabilities of staff from the Office of Livestock and Pasture (OEP) and the Commissariat Regional de Développement Agricole (CRDA) in vegetation cover survey and management. Objectives included gaining knowledge in environmental sciences, acquiring skills for data collection and analysis, and determining carrying capacity for suitable grazing management.